Main factors of ineffectiveness of the criminal procedure standard that it has to request as an advance proof statement of victims of the crime of sexual indemnity, Tacna – 2017 - Aro Mamani, Henry Douglas (2020)
Investigation developed with the purpose of knowing which are the main factors that render ineffective the anticipated proof in the crime of sexual indemnity specifically in the declaration that the victim offers through his request by the legitimate parties. Mixed type research with a non-experimental observational design and a descriptive level. The intentional sample was made up of 67 lawyers and 2 prosecutors in which they were interviewed using the semi-structured interview guide. To the main conclusions is that there was a divergence of considerations on the part of lawyers and prosecutors. Prosecutors believe that Article 242 should be amended in order for there to be an update. The non-use of the criminal procedural rule and the fiscal and defense strategy on the theory of the case are the main influencing factors